(untitled) (Bangladesh Journal of Neurosurgery, 2024)
Digital Subtraction Angiography (DSA) is a modern technique which integrates digital data collection and computer processing to produce a medical image. X-ray signals are detected electronically rather than on film and then converted to digital form to be processed by a computer before being displayed. DSA is an integral investigation in the management of patients with neurovascular diseases. It is basically used for diagnosis, but in many instances, it may be therapeutic in the same sitting. Indications for diagnostic DSA include both extracranial and intracranial vascular diseases. A sound understanding of the principles of appropriate periprocedural care and anatomy, catheter technique and basic disease pathology are vital to use DSA as a diagnostic as well as therapeutic purposes. Bang. J Neurosurgery 2023; 12(2): 102-113